The impact of court on children: research findings and practical recommendations - Lipovsky, J. A. (Journal of interpersonal violence, 1994)
Concerns about possible negative impacts to children as a result of participating in the criminal justice system have led to discussions about altering the process in ways that accommodate the specific developmental and emotional needs of children. However, before making major changes to the system, it is essential to answer several questions. This article reviews research addressing the following questions: (a) How frequently do children testify in court? (b) Is involvement in the criminal justice system, particularly providing testimony in criminal court, harmful to child witnesses? (c) Do suggested innovations in practice reduce children's court-related distress? Research findings related to these questions are then discussed in terms of their application to practice with children as witnesses within the criminal justice system